Assessment of Time and Cost Overrun of Province Level Construction Project in Tanahun, Gandaki Province, Nepal - Gautam, Homnath; Gurung, Som; Ghimire, Krishna (Journal of Engineering Issues and Solutions, 2026)
The most prevalent issues that have a significant negative influence on the project and the parties involved are time and cost overrun. In Nepal, the construction industry is frequently facing various problems, including cost, quality and time. The study’s primary objective is to identify the main causes contributing to time and cost overrun in execution of construction Project. The study includes detail on the completed multiyear province level construction projects that were implemented in Tanahun district from fiscal year FY 2075/76 - FY 2079/80 through National Competitive Bidding (NCB) to analyze time and cost overrun. Also, a review of the literature was done to determine the 78 causes of time and cost overrun and the 17-mitigation measure of those time and cost overrun. Technical client representatives, consultants, and contractors were surveyed using a questionnaire to get their opinions on the causes and mitigation measures. Based on the responses of 71 respondents five most significant causes of time and cost overrun according to the Relative Importance Index (RII) and focus group discussion were: 1) Poor controlling of sub-contractor(s) by the contractor, 2) Improper technical studies by the contractor during the bidding stage, 3) Poor communications and misunderstanding, 4) Low bidding of contract, 5) Unavailability of construction material testing lab. Five main mitigation measure for time and cost overrun were: 1) Selecting a consultant who has sufficient experiences in similar nature of works and has good reputation, 2) Develop competent teams for executing works, 3) Effective planning and scheduling, 4) Select experienced and capable subcontractors, 5) Development of a proper system of site management and supervision. Among 15 multiyear construction projects of Tanahun district undertaken under NCB, 11 projects (80.00%) experienced time overrun. Time overrun range from 21.21% % to 304.38%.. Risti khola bridge (Sotibesi) of 21.21% % due to omission of quantityinoriginalBOQandRoadwayUpgradingWorksalongKalimatiDudhekunaManechauka experienced the highest cost overrun of 304.38% due to the COVID- 19, monsoon, lack of budget and site possession. Also, five of them experienced the cost overrun and among them Risti khola bridge (Sotibesi) faced the highest cost overrun of 11.58% due to additional work and omission of quantity in original BOQ. Analysis of result shows that collective effort between all parties is required to reduce delay. Therefore, separate recommendations are provided to clients, consultants and contractors.